Analysis of Specific Th1/Th2 Helper Cell Responses and IgG Subtype Antibodies in Anti-CD4 Monoclonal Antibody Treated Mice with Autoimmune Cardiomyopathy - 汪朝晖 廖玉华 袁璟 张景辉 董继华 王金平 (Journal of Huazhong University of Science and Technology. Medical sciences, 2008)
The cytokine repertoire of ADP/ATP carrier-specific humoral immune responses and the cytokine-dependent anti-ADP/ATP carrier antibody IgG subclasses were examined in a cohort of ADP/ATP carrier-immunized BALB/c mice treated with anti-CD4 monoclonal antibody. Eighteen male BALB/c mice （6–8 weeks old） were randomized into 3 groups： dilated cardiomyopathy （DCM） group, DCM-tolerance （Tol） group and control group. The mice in DCM group were immunized with the peptides derived from human ADP/ATP carrier protein for 6 months and mice in the control group were sham-immunized, while the mice in DCM-Tol group were immunized with ADP/ATP carrier protein and anti-CD4 McAb simultaneously. Serum autoantibody against ADP/ATP carrier and IgG subclasses were measured by ELISA, intracellular cytokines IFN-γ and IL-4 of Th cells were moni- tored with flow cytometry, and splenic T cell cytokines IFN-γ, IL-2, IL-4 and IL-6 were detected by using real-time fluorescent quantitative PCR. The results showed that the autoantibody against ADP/ATP carrier was found in all mice in DCM group, and the antibody level, serum IgG1 and IgG2a subclasses, cytokines in T cells and Th cells were all elevated in DCM group, as compared with those in control group （P〈0.01）. On the other hand, in DCM-Tol group, the autoantibody level and contents of all the cytokines were significantly different from those in DCM group （P〈0.01）, and were close to those in control group. And the levels of IgG1, IgG2a, IgG2b and IgG3 were influenced, to varying degrees, by anti-CD4 McAb as compared with those in DCM group. All these four types of IgG subclasses were substantially decreased in DCM-Tol group as compared with DCM group. It is concluded that the treatment with anti-CD4 McAb could prevent the activation of T cells, reverse the abnormal secretion of cytokines and the imbalance between Th1/Th2 cell subsets and abnormal production of autoantibody against ADP/ATP carrier, and eventually avoid myocardial injuries.